Disjunct resident population of Melodious Lark Mirafra cheniana discovered in East Africa - Brian W. Finch; R. Stratton Hatfield; Silvia Colombo; Adam S. Kennedy; Marije te Raa; Martin Irestedt; Dawid H. de Swardt; Joe Grosel; Derek Engelbrecht; Callan Cohen; Urban Olsson; Paul F. Donald; et al. (Journal of Ornithology, 2023)
We describe the discovery of a previously unknown population of Melodious Lark Mirafra cheniana from northern Tanzania and southern Kenya, some 2000 km north of what was previously thought to be its northern limit in central Zimbabwe. The identification of this population as M. cheniana is based primarily on analyses of mitochondrial DNA and song. We also clarify relationships within this genus by sequencing material of White-tailed Lark Mirafra albicauda for the first time; although its relationships with other species in the group remain unclear, our analyses clearly show it to be different from M. cheniana in the newly discovered population. The discovery of a population of M. cheniana in East Africa conforms to a known pattern for closely related lark species to have disjunct distributions in southern and eastern Africa.

Galagos as avian nest predators in South Africa - Derek Engelbrecht (Primates, 2016)